1995
DOI: 10.1074/jbc.270.28.16871
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated Oligosaccharides Promote Hepatocyte Growth Factor Association and Govern Its Mitogenic Activity

Abstract: Hepatocyte growth factor (HGF) is a potent mitogen, motogen, and morphogen for various epithelial cell types. The pleiotropic effects of HGF are mediated by its binding to a specific high affinity receptor, c-Met. In addition, HGF binds to heparan sulfate proteoglycans on cell surfaces and within the extracellular matrix. Incubation of HGF with 0.1, 1.0, and 10 micrograms/ml of heparin, heparan sulfate, or dextran sulfate resulted in a concentration-dependent increase in mitogenic potency in a primary rat hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
128
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(135 citation statements)
references
References 36 publications
6
128
0
1
Order By: Relevance
“…In that system, added heparin facilitates HGF signaling (11), through a mechanism that was presumed to involve its demonstrated ability to enhance HGF oligomerization (12,18,19). Despite its inability to bind heparin, we found that K1 mitogenic signaling in 32D/c-Met cells was completely heparin-dependent.…”
mentioning
confidence: 62%
“…In that system, added heparin facilitates HGF signaling (11), through a mechanism that was presumed to involve its demonstrated ability to enhance HGF oligomerization (12,18,19). Despite its inability to bind heparin, we found that K1 mitogenic signaling in 32D/c-Met cells was completely heparin-dependent.…”
mentioning
confidence: 62%
“…The augmentation of Akt phosphorylation levels by heparin (Fig. 3, C and D) may suggest the existence of a specific heparanase receptor that, similar to several growth factor receptors, requires heparin to exert maximal activities (31,35,36). Studies aiming to identify this putative heparanase receptor are currently in progress.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, some may be considered "HS-dependent", since in vitro manipulations that remove, or prevent the sulfation of, cellular HS result in greatly decreased growth factor binding to, and activation of, signaling receptors. The best characterized HS-dependent growth factors are FGF-1 and FGF-2, but other FGFs, HB-EGF, wingless (a member of the Wnt family) and probably several other growth factors belong to this group (Rapraeger et al, 1991;Yayon et al, 1991;Aviezer and Yayon, 1994;Tessler et al, 1994;Zioncheck et al, 1995;Reichsman et al, 1996). Models that have been put forth to explain HS-dependence include ones in which binding of HS to growth factor, receptor, or both directly alters affinity (e.g., through cross-linking, dimerization, or induction of a conformational change [Kan et al, 1993;Pantoliano et al, 1994;Spivak-Kroizman et al, 1994]).…”
Section: Rotes Of Pgs In Growth Factor Signatingmentioning
confidence: 99%